2005
DOI: 10.1111/j.1523-1755.2005.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of quantitative BOLD MRI measurements in kidney: Application to unilateral ureteral obstruction

Abstract: BOLD MRI provides noninvasive estimates of regional renal oxygen content and our study demonstrates that this technique may provide a useful tool in UUO which is associated with altered renal oxygen consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
153
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(161 citation statements)
references
References 32 publications
5
153
1
2
Order By: Relevance
“…Therefore, the present study was designed to test the hypothesis that despite proportional changes in whole kidney O 2 delivery and consumption, acute progressive renal arterial stenosis (RAS) leads to decreases in regional renal tissue oxygenation. To test this hypothesis and determine whether stoichiometric energy requirements are altered, we assessed changes in renal O 2 consumption, arteriovenous O 2 differences, and sodium reabsorption, and we concurrently measured intrarenal tissue oxygenation directly with oxygen electrodes (17,21,25) during acute RAS.…”
mentioning
confidence: 99%
“…Therefore, the present study was designed to test the hypothesis that despite proportional changes in whole kidney O 2 delivery and consumption, acute progressive renal arterial stenosis (RAS) leads to decreases in regional renal tissue oxygenation. To test this hypothesis and determine whether stoichiometric energy requirements are altered, we assessed changes in renal O 2 consumption, arteriovenous O 2 differences, and sodium reabsorption, and we concurrently measured intrarenal tissue oxygenation directly with oxygen electrodes (17,21,25) during acute RAS.…”
mentioning
confidence: 99%
“…It was demonstrated recently in animals that acute experimental reduction of renal perfusion pressure, with subsequent reduction of renal blood flow, diminishes the renal blood oxygenation level-dependent (BOLD) MRI signal. 7,8 BOLD MRI exploits the fact that the different magnetic susceptibilities of oxygenated and deoxygenated hemoglobin result in locally different effective transversal relaxation rates. Therefore, changes in tissue oxygenation can be detected by BOLD MRI via altered concentrations of deoxyhemoglobin.…”
mentioning
confidence: 99%
“…The validity of the BOLD signal for monitoring of renal oxygenation has been investigated in animal studies: Renal BOLD MRI was demonstrated to reflect oxygen consumption in pigs by comparison with oxygen partial pressure (p O 2 ) measurements performed with oxygen-sensitive microelectrodes [31].…”
Section: Applicationsmentioning
confidence: 99%
“…Pedersen et al [31] DWI diffusion-weighted imaging, DTI diffusion tensor imaging, ASL arterial spin labeling, BOLD blood oxygen level dependent…”
Section: Animal Study Dwi/ Dtimentioning
confidence: 99%